Genocide, joint criminal enterprise, and reconciliation: Interactional analysis of a post-war society in the context of legitimizing transitional capitalism - Zlatan Delić; Goran Basic (Cogent Social Sciences, 2024)
The war in Bosnia and Herzegovina (1992–1995) is the historic background of this paper, as produced in the documents presented during international and national trials concerning war crimes committed during this period. A literature review forms the analytical basis and contains various empirical and theoretical studies from the fields of philosophy, war sociology, and social epistemology. The aim of this paper is to analyse the normative orientations and social values that affect (1) the feelings of moral and social understanding (or non-understanding) after the genocide and the joint criminal enterprise in Bosnia and Herzegovina in the context of legitimizing transitional capitalism, (2) the actions of individuals, organizations, and states as well as the entire social community in the post-war society, and (3) the process of reconciliation and trust in post-war society. The analysis makes evident the usual tendency in a post-war society to deify one’s own ethnic (religious) group, while the consequence of such false self-infatuation with “our” collective is that the “other” that is not ours becomes undesirable. It must be, as evidence of patriotism and unconditional emotional loyalty to “our holy issue”, wiped out for good. Ethnic cleansings, joint criminal enterprises, and genocides thus become a normal means of ethnopolitical—i.e. biopolitical—“management of differences”. At the same time, ethnocorruption and ethnobanditry can erroneously be qualified as the least transparent and, for social and criminological research, the most difficult phenomena (or manifestations) of social pathology. The difficulty lies in the fact that ethnocorruption and ethnobanditry are in many respects related and intertwined with the simultaneous institutional and organizational processes of regulating (or not regulating) the economic and political globalization and transfer of ownership during the transition from socialist self-management to a new type of economy.